Migração e seletividade no mercado de trabalho de Fortaleza: uma análise econométrica - Miranda, Keyla Christina Albuquerque (2004)
The main objective of this paper is to revearch the existence of positive ou negative selectiviness of migrant workers from Ceará state country side; that search better life condicions, specially better wages in Fortaleza’s job market. This research used monthly data available from SINE/IDT – CE (Nacional Suployment and Subemployment System / Work Developemnt Institute – Ceará).This data will main it possible to observe the varius caracteristics of the samples such as: salary, marital status, sex, age, education level, work experience, hours worked per week, etc, e and to test ramdomly by existence os selectiveness of the migrant work force in Fortaleza’s job market